Copolymerization of D,L-lactide and ε-caprolactone using tin(II) octanoate as catalysts: an insight into copolymer microstructure - Kostjuk, Sergei V. (Journal of the Belarusian State University. Chemistry, 2020)
Sn(Oct)2-catalyzed ring-opening copolymerization of D,L-lactide and e-caprolactone in bulk at 130 °C at different D,L-lactide/e-caprolactone has been studied. It was shown that independent on the initial comonomers ratio, the synthesized copolymers are enriched by D,L-lactide at the early stage of reaction indicating the formation of gradient-like copolymer. However, the intensive transesterification reaction both during the polymerization and at the monomer-starved conditions leads to the redistribution of the monomer sequences and formation of the random copolymer. The synthesized copolymers are characterized by high polydispersity (Đ > 2.0), which raises when the reaction mixture was kept under monomer-starved conditions that confirms the occurrence of transesterification. The formation of random copolymer is confirmed by single Tg value, which gradually increased with the increase of the amount of D,L-lactide in the copolymer from –48.6 °C to 33.3 °C for D,L-lactide/e-caprolactone ratio in copolymer of 20:80 and 90:10 mol/mol, respectively.
Keywords: ring-opening copolymerization; D,L-lactide; ε-caprolactone; tin(II) octanoate; biodegradable copolymers